2017
DOI: 10.1177/2041669517726797
|View full text |Cite|
|
Sign up to set email alerts
|

Yawning Detection Sensitivity and Yawning Contagion

Abstract: Contagious yawning—the urge to yawn when thinking about, listening to, or viewing yawning—is a well-documented phenomenon in humans and animals. The reduced yawn contagion observed in the autistic population suggested that it might be empathy related; however, it is unknown whether such a connection applies to nonclinical populations. We examined influences from both empathy (i.e., autistic traits) and nonempathy factors (i.e., individuals’ perceptual detection sensitivity to yawning, happy, and angry faces) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 84 publications
(132 reference statements)
3
21
0
Order By: Relevance
“…The highest levels of auditory yawn contagion in women compared to men confirm the gender bias observed in naturalistic conditions on humans susceptible to yawn contagion by Norscia et al (2016a,b) when considering a larger dataset that also included yawns that could be seen by the potential responder (with yawning sensory modality-vision, hearing, or both-not affecting the response). The gender bias is also in partial agreement with previous results obtained in controlled settings, including the visual cue (Chan and Tseng, 2017; but see Norscia and Palagi, 2011;Bartholomew and Cirulli, 2014). It has been hypothesized that the high degree of yawn contagion in FIGURE 3 | Line plot of the effect of the sex of the responder (X-axis) on acoustic yawn contagion mean occurrence (Y -axis).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The highest levels of auditory yawn contagion in women compared to men confirm the gender bias observed in naturalistic conditions on humans susceptible to yawn contagion by Norscia et al (2016a,b) when considering a larger dataset that also included yawns that could be seen by the potential responder (with yawning sensory modality-vision, hearing, or both-not affecting the response). The gender bias is also in partial agreement with previous results obtained in controlled settings, including the visual cue (Chan and Tseng, 2017; but see Norscia and Palagi, 2011;Bartholomew and Cirulli, 2014). It has been hypothesized that the high degree of yawn contagion in FIGURE 3 | Line plot of the effect of the sex of the responder (X-axis) on acoustic yawn contagion mean occurrence (Y -axis).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, yawn contagion is neither sensitive to the sensory cues present in the signal (auditory, visual, or audio-visual) (Arnott et al, 2009;Norscia and Palagi, 2011) nor affected by the visual perspective of the triggering stimulus (yawns in orientations of 90 • , 180 • , and 270 • are able to trigger yawning responses as frontal, 0 • yawns; Provine, 1989Provine, , 1996. Chan and Tseng (2017) found that the ability to detect a yawn as such (perceptual detection sensitivity) was related to the duration of gaze to the eyes of the stimulus releasing face, but eye-gaze patterns were not able modulate contagious yawning. In chimpanzees, contagious yawning frequencies were highest between same-group than different-group individuals, even if the responders looked longer at out-group chimpanzee videos (Campbell and de Waal, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The OLS coefficient indicates that females are on average 0.59 standard deviations higher on the IRI as compared to males, which mirrors the results of other studies (e.g. Chan and Tseng 2017, Norscia et al 2016a, Willer et al 2015).…”
supporting
confidence: 85%
“…In humans, a certain degree of difference may be present in yawn contagion between men and women but the issue is still under debate (Chan and Tseng, 2017;Norscia et al, 2016a,b; but see Bartholomew and Cirulli, 2014). The cultural influence in shaping relationship dynamics in the different human societies makes it difficult to disentangle social bonding and gender effects in the distribution of yawn contagion.…”
Section: From Yawn Contagion and Mimicry To Emotional Contagion In Nomentioning
confidence: 99%
“…found that yawn contagion in ASD children was positively correlated to the blood concentration of oxytocin, the hormone involved in parental and social attachment (Decety et al, 2016). In nonclinical human subjects, Chan and Tseng (2017) found that the perceptual detection sensitivity to yawning expression (the ability to detect a yawn as such) was related to the duration of gaze to the eyes of the stimulus releasing face, but the authors failed to find evidence that eye-gaze patterns modulated contagious yawning.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%